Etno-fotografi ketahanan eko-budaya Selorejo untuk mata kuliah Pendidikan Kewarganegaraan - Andhika Yudha Pratama; Adinda Dwi Larasati; Alfian Fawaidil Wafa; Dini Putri Ratna Meritasari; Satifa Agatha (Curricula: Journal of Curriculum Development, 2026)
The integration of indigenous knowledge (local wisdom) into environmental conservation represents a crucial evolution in the cycle of civilization. This is evidenced by the growing public recognition of authentic ecological insights and sustainable practices preserved by indigenous peoples worldwide, particularly in relation to ecosystem balance, over many years through the tradition of “Wong Ireng”. This study focuses on the development of reflective educational media with aesthetic value, specifically an ethnophotography book on the eco-cultural life of the Selorejo Village community. This research aims to increase awareness and knowledge among the younger generation in Selorejo Village. This research employs the 4D development research method, which comprises four stages: Define, Design, Development, and Disseminate. The development of the Selorejo Cultural Ecology ethnographic photography book was implemented in Pancasila and Citizenship Education as a learning medium for students. This book provides fresh and informative insights for the general public, using easy-to-understand language, and describes both the culture and social characteristics of the Selorejo community.